Confronting Violence in the Novel Between the World and Me (2015) by Ta-Nehisi Coates - Hasbi Hasbi; Leni Marlina (Universitas Negeri Padang, 2020)
This thesis is the analysis of the novel Between the World and Me (2015) by Ta-Nehisi Coates. The topic explain how the character tries to deal with violence perpetrated by White. The problem of this analysis is to what extent the novel reveals the character’s attempts to deal with the subtle violence against black people, and how much fictional devices such as setting, character and conflict have an effect of showing the character’s efforts to deal with violence. The purpose of this analysis is to reveal the character’s efforts against violence done by white, and determine the role of character, setting and conflict in helping to know the character’s efforts to deal with violence. The theory in this analysis is the concept of self-awareness by Duval and Wicklund. The method is text-based interpretation and context-based interpretation. The results of this analysis shows that the character’s efforts in dealing violence can save him from death. In other words, black can survive from violence by trying to face and fight the violence itself.Key words: Violence , Black, Self-awareness